Analysis of Environmental Carrying Capacity and Environmental Accompany Based on Ecosystem Services in Cultivation Areas in The Bengkayang Regency RTRW 2025-2045 - Widiarso, Bambang; Riduansyah, Riduansyah; Junaidi, Junaidi; Agustine, Leony (Jurnal Biologi Tropis, 2025)
The preparation of regional spatial plans must be guided by the analysis of environmental carrying capacity and carrying capacity, the method of measuring environmental carrying capacity and carrying capacity based on ecosystem services with a spatial approach has a more appropriate use value. This study aims to identify and analyze the environmental carrying capacity and carrying capacity based on ecosystem services in the RTRW Cultivation Area of ​​Bengkayang Regency in 2025-2045. The research method uses the main basic data approach, namely the characteristics of the landscape ecoregion, natural vegetation communities, and land use. Data analysis uses expert-based evaluation methods, pairwise comparisons, and weighted sums to obtain the value of the ecosystem service index. The results of the study obtained water carrying capacity in accordance with the Decree of the Minister of Environment and Forestry No. 146 of 2022, the carrying capacity of water supply ecosystem services is dominated by the medium category of 61.126%, the carrying capacity of food supply services is high category 54.20%, the carrying capacity of climate regulation ecosystem services is dominated by the high category 54.83%, the carrying capacity of disaster protection ecosystem services is dominated by the high category 77.64%, the carrying capacity of flora and fauna supporting ecosystem services is dominated by the low category 88.73%, and the carrying capacity of genetic resource providing ecosystem services is dominated by the high category 63.75%. The conclusion is that the cultivation locations in the Bengkayang Regency RTRW for 2025-2045 are generally in accordance with the carrying capacity and environmental capacity based on ecosystem services.